Early diagnosis improving the outcome of an infant with epileptic encephalopathy with cytoplasmic FMRP interacting protein 2 mutation: Case report and literature review - Zhong, Min (Medicine (Baltimore), 2019)
RATIONALE: Early infantile epileptic encephalopathy (EIEE) 65 was recently shown to be caused by the cytoplasmic FMRP interacting protein 2 (CYFIP2) mutation. To date, only 5 cases have been reported in two articles, and all the outcomes in all cases were poor. PATIENT CONCERNS: In this study, we reported an 8-month-old girl with a 1 month-long history of seizures and developmental delay. Over 1 month later, she developed epileptic spasms in clusters with hypsarrhythmia on electroencephalography. DIAGNOSIS: The patient was diagnosed with EIEE 65 and trio-based whole-exome sequencing revealed a causative de novo CYFIP2 mutation c.260G >T (p.Arg87Leu). INTERVENTIONS: The proband was successively treated with multiple antiepileptic drugs, including levetiracetam, phenobarbital, VitB6, topiramate, methylprednisolone, prednisone, valproic acid and vigabatrin. OUTCOMES: After resistance to multiple anti-epileptic drugs over 2 months of treatment, she finally achieved seizure-free several days after vigabatrin administration and her developmental delay steadily improved. LESSONS: OUR: case confirmed that CYFIP2 was the pathogenic gene of EIEE 65. We also first demonstrated vigabatrin might be effective for control of seizures and helpful for the improved outcomes of these patients.